Une revue de laboratoire de l’électronique au diamant : e-Rea et vingt ans de science ouverte - Anne DUNAN-PAGE (E-REA)
e-Rea has gone through two major periods in its history: the first, which could be described as a gestation period (2003-2008), during which this new journal had to find its readership, experiment with new formats and adopt good editorial practices; and a second one, which corresponded to the journal’s accession to OpenEdition, following a new editorial departure (in 2008). This was not simply a technical transition, from the servers of the former Université de Provence to an international portal in HSS that specializes in open science. It has left a deep impact on the journal’s objectives and development. This evolution has also led to a rethinking of the journal’s environment, with repercussions in terms of teaching and research. This contribution examines the way an academic journal such as e-Rea initiated a long-lasting reflection on open science, among researchers, as well as students. In doing so, it replaces e-Rea within earlier publications in English Studies at Aix-en-Provence.